ANALYSIS OF SEISMIC FRAGILITY CURVE ON EXISTING BUILDING AND BUILDING WITH ADDITION OF BASE ISOLATION - Lidwina Andriani, Alicia
Indonesia is a country with a high level of vulnerability to earthquake. Several existing structures have not been fully designed according to the latest earthquake provisions. Past provisions such as PBI-1971 and PMI-1971 are relatively less conservative than current seismic provisions. Indonesia's high level of vulnerability to earthquakes requires several major infrastructures to be able to survive when an earthquake occurs. For this reason, it is necessary to analyze the vulnerability of structures designed with old provisions with future earthquakes. One method that can be used to analyze the vulnerability of a structure due to earthquake forces is to form a structure fragility curve. The fragility curve of the structure will show the level of vulnerability of the structure to various intensity of earthquake forces. When developing the structure fragility curve, time history analysis method will be used. Ground motion records that used in time history analysis will be scaled first to the response spectrum of Bandung. The structure is 3D modelled so ground motion record will be used for the x-direction and the y-direction. The fragility curve of structure will also be different for the x-direction and the y-direction. FEMA 356 criteria on structure performance level will be used to determine the performance level of structure. The development of structure fragility curve will also be performed for the structure with improvements of double friction pendulum system (DFPS) type base isolation. The development of structure fragility curve with non-linear time history analysis (NLTHA) will be using 8 pairs of ground motion records. The structure will then be analyzed using the incremental dynamic analysis (IDA) method by gradually increasing the intensity of the earthquake to obtain failures at each structural performance level. With structure fragility curve, the performance of the structure against earthquake loads with a certain intensity can be determined. The fragility curve of the structure can also show the effect and performance of base isolation on the structure on improving the structural performance against earthquake forces.